Pengaruh Pendidikan dan Pelatihan Serta Promosi Jabatan dalam Meningkatkan Kinerja Tenaga Kependidikan Non PNS - Dari, Eva Wulan; Gani, Abdul Juli Andi; Noor, Irwan (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2022)
Work performance is a crucial variable that remains relevant to be discusse asevery company is expected to have excellent performance. This study aims to investigate the effect of promotion, education, and training programs on the performance of non-civil servant academic in Faculty of Engineering, UB. This study implements a survey method with a quantitative approach and the research sample included 72 respondent,selected with non-probability sampling. Data were collected by questionnaire, which had previously been tested for validity and reliability. Hypotheses were tested using multiple regression. Based on the results, education and training, and promotions proved to have a significant effect on the performance of non-civil servant academic staff with 84.2% contribution. This finding is an important recommendation for the faculty to provide education and training programs regularly to maintain and improve employee competence. Furthermore, faculty may consider providing promotion programs to motivate the staff to dedicate their best performance.